Meningkatkan Kebhinekaan Global dengan Metode PBL Fase D Kelas IX SMP Santo Kristoforus I Jakarta - Petrus Laritmas; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The results of reflection on the learning outcomes of grade IX students showed that there were problems with affective aspects and cognitive aspects that affected their learning achievement. This problem arises because one of the causes is that teachers are less varied in using learning methods. The method used is still lecture. From these problems, the objectives of this research are: 1) improving student learning achievement with material on the Catholic Church's attitude towards religion and other beliefs which is reflected in their learning achievement that is still lacking, 2) improving the character of students' global diversity through the problem based learning (PBL) method. This classroom action research was carried out in four stages, namely planning, implementation, evaluation, and reflection with 29 students in class 9A. The research was carried out in two cycles. This research focuses on the diversity dimension of the Pancasila Student Profile (P3). Data analysis was carried out with a percentage description to measure aspects of diversity with observation and learning achievement with the final test in each cycle. The results showed that there was an increase in learning achievement from cycle 1 to cycle 2 by 20%. The results of the cognitive aspect test showed that the average learning achievement score from cycle 1 was proficient 17%, proficient 27%, and proficient 20%, increasing to proficient 72%, proficient 27%, and proficient 0% in cycle 2. Meanwhile, in the aspect of diversity, it showed an increase from 68.49% to 84.58%. There was a 16% increase. The results of the reflection recommend that there needs to be affective aspect assistance for students so that it can increase student learning independence. The conclusion is that learning with the PBL method by focusing on one dimension of P3 can increase student learning independence.